Geochemistry, geochronology, and tectonic significance of diorite porphyry from the Northern Daheishan Horst in NE China - Li, Jie; Wang, Qi; Li, Mengxia; Jiang, Shan; Han, Jing; Guan, LinXuan; Yu, Yinghua; Yuan, Hongqi (Frontiers in Earth Science, 2025)
The Daheishan Horst is located in the eastern segment of the Solonker-Xar Moron River-Changchun-Yanji Suture (SXCYS), between the eastern margin of the Songliao Basin and the Jiayi Fault Zone. The Daheishan Horst serves as a critical area for studying the evolutionary processes of the eastern Paleo-Asian Ocean (PAO). Current debates persist regarding the formation age, tectonic setting, and evolution of magmatic rocks in the Daheishan Horst. To address these controversies, this study examines diorite porphyry dikes exposed in Heibei Village, Jilin City, Jilin Province, through comprehensive analyses including: whole-rock major, trace, and rare earth elements; zircon U-Pb dating; zircon Hf isotopes; and whole-rock Sr-Nd isotopes. These investigations aim to determine the formation age and tectonic evolution of the magmatic rocks in the Daheishan Horst. Key findings include: (1) Zircon U-Pb ages (252.9 ± 3.2 Ma) indicate Late Permian emplacement; (2) The magmatic rocks are predominantly subalkaline and belong to the medium-K calc-alkaline series. They exhibit enrichment in large-ion lithophile elements (LILEs) and light rare earth elements (LREEs), with significant depletion in high-field-strength elements (HFSEs: Nb, Ta, P, Ti), consistent with arc-type or active continental margin magmatism; (3) Zircon Hf and whole-rock Sr-Nd isotopic analyses indicate magma derivation primarily from partial melting of depleted mantle sources, with negligible contamination from ancient crustal materials; (4) Geochemical signatures include positive La/Sm-La correlations, elevated Th contents (6.21–11.66 ppm), Th/Yb = 2.52–3.66, Zr/Y = 9.7–11.5, and Ta/Yb = 0.12–0.28. These features are diagnostic of oceanic-continental subduction zone magmatism, confirming origination from partial melting of subduction-fluid-metasomatized mantle. This study concludes that the magmatic rocks of the Daheishan Horst formed during subduction beneath an active continental margin. Our results reveal a bidirectional subduction with scissor-like closure model along the SXCYS in the eastern Paleo-Asian Ocean, with closure propagating westward to eastward from the Late Permian to Early/Middle Triassic.